Spine arrangement during work in sitting position and occurrence of pain among dentists and medical assistants - Olga Nowotny-Czupryna; Krzysztof Czupryna; Małgorzata Skucha-Nowak; Joanna Szymańska (Nofer Institute of Occupational Medicine, 2018)
Background Back pain is common among people working in the sitting position. Quality of the sitting position depends among others on the standard of work station. Dental units are built on the basis of contemporary ergonomic workplace concepts, while medical assistant workstations are typically computer office workstations. The purpose of the study was pain estimation in association with the identification of the spine arrangements during sitting work with better and worse ergonomic adjustment. Material and Methods The study involved 80 women working in the sitting position suffering from pain - 40 dentists working on dental units with a higher ergonomic potential and 40 medical assistants working on stations with lower ergonomic potential. The study included interviews, pain assessment and working spine arrangements analysis using the ultrasonographic measurement system. Results There were exceeds of work parameters in particular segments of the spine observed in all examined persons. The relationship between pain intensity and work parameters as frontal bending amplitude of lumbar spine segment, transversal amplitude of cervical spine segment and transversal amplitude of lumbar spine segment were observed in the group of dentists. There was observed the relationship between pain severity and the values of sagittal bending amplitude of cervical spine segment and thoracic spine segment in the group of medical assistants. Other determinants of pain also have been identified. Conclusions Exceeded values of work parameters were observed amongst subjects working both at the higher and the lower ergonomic potential work stations. The working postures of people working in the sitting position are similar only to their external characteristics. Pain depends on working position. The pain intensity is determined by other factors: length of professional experience, duration of the pain, the number of working hours per week, body mass index (BMI). Med Pr 2018;69(5):509-522